Izolacja skazanych niebezpiecznych w polskich zakładach karnych - Ćwikła, Monika (Kortowski Przegląd Prawniczy, 2021)
The article is about dangerous perpetrator in the conditions of penitentiary isolation. It contains the ways of defining, qualifying dangerous perpetrator and also information and a photo the prison room for the detainee. The article also contains statistical data showing the number of prisoners qualified to perpetrators ”N” in the period 2016–2017 and data on the number of existing penitentiary units intended for this type of perpetrators. Attention was also paid to the problem of results of conducting such isolation for a long period of time. The aim of this article was to summarize and outline the problem of long-term prison isolation and its consequences for inmates, as well as to indicate the existing legal provisions and classification as a dangerous perpetrator.